PENGARUH APLIKASI BERBAGAI JENIS INSEKTISIDA TERHADAP ULAT BAWANG (Spodoptera exigua Hubn) DAN PRODUKSI BAWANG MERAH VARIETAS BIMA DAN TINOMBO - Shahabuddin Shahabuddin; Mahfudz Mahfudz (Universitas Tadulako, 2010)
This study aimed to examine the effect of various insecticides against beet armyworm pest (S. exigua) and onion yield. The experiment were conducted in Poso district and arranged using a randomized block design (RBD) with two-factor treatment and tree replicates each. The first factor was the type of Insecticides (I) consists of three treatments and one control, namely: (1) No insecticides (I0), (2) botanical insecticides (neem leaf extract) 50 g/l of water (I1). (3) Biological insecticides, the fungus Beauveria bassiana 10 g/l of water (I2) and (4) chemical insecticides, Klensect 200 EC 1 ml/l of water (I3). The second factor was onion varieties composed of: (1) Bima (V1) and (2) Tinombo (V2) vartieties. Variabel measured included: S.exigua population density, percentage of attacks of S.exigua, and dry weight of tuber. The results showed that insecticides treatment significantly affected the population density and S.exigua attacks on onion crops in the district of Poso. The effectiveness of chemical and botanical insecticides on suppressing the population density and the attack of S. exigua were nearly similar and significantly higher than that of biological insecticide. The population density and percentage of S. exigua attacks did not differ significantly in both varieties but dry weight of tuber was higher in Bima variety. There was no interaction effect between insecticides and onion variety on population density and attack percentage of S. exigua as well as on tuber weight.